PENGARUH HAMBATAN SAMPING TERHADAP KINERJA LALU LINTAS JALAN NASIONAL (Studi Kasus Jalan Raya Mondoroko – Pasar Singosari Malang)The main road of Pasar Singosari is an arterial road connecting Surabaya and Malang. The increasingly crowded activities that - Mohammad Husin; Dian Kusumaningsih (CV SWA Anugerah, 2023)
The main road of Pasar Singosari is an arterial road connecting Surabaya and Malang. The increasingly crowded activities that occur in Singosari Market, such as vehicle density, angkot that drops off passengers, parking on the shoulder of the road and other side obstacles affect the performance of the main road section in the market area. This research uses a method by processing primary data from field surveys and collecting some information needed as secondary data. From the results of the analysis, it was found that the side resistance was quite high (H) = 729. For the ability of the Mondoroko highway section can pass the amount of traffic volume C = 4116.82 smp/hour, The Mondoroko highway section is said to experience problems with its saturation capacity which almost exceeds the ideal saturation degree limit DS = 0.75 – 0.80. On Sundays and Saturdays the south direction is still under normal circumstances 0.65 service level C